PENERAPAN PROGRAM AKSELARASI DALAM MENINGKATKAN MUTU PENDIDIKAN DI MA PK AL AMIN KOTA TASIKMALAYA - Sukma Jayanti, Nur Asti; Komalasari, Imas; Abdussalam, Aam (An-Nahdliyyah: Jurnal Studi Keislaman, 2024)
Improving the quality of education is important, one of which is by managing all educational resources to produce appropriate educational services. The provision of education today is more of a mass classical nature which is quantity oriented which causes the individual needs of students outside of the normal student group to not be accommodated. Implementing an acceleration program can be an effort to accommodate students' needs according to their potential and talents. This research aims to determine the application of the acceleration program in improving the quality of education at MA PK Al-Amin, Tasikmalaya City. This research uses a qualitative approach with data analysis techniques consisting of data reduction, data display and data verification. The results of the study indicate that the implementation of the acceleration program at MA PK Al-Amin is running quite optimally and has an impact on improving the quality of education, namely: 1) the acceleration program at MA PK Al-Amin Tasikmalaya City is running quite optimally through (a) identification of talented children with written tests, oral tests, and interviews, (b) determination of handling strategies with superior programs, (c) development of educational programs with selection of majors and universities, (d) educational services through continued assistance, (e) building and developing learning resources in preparation for learning. (2) The quality of education is implemented with 8 supporting factors, namely (a) input (input, intake) of educators and students, (b) curriculum with an accelerated learning system, (c) potential educators/teachers, (d) complete facilities and infrastructure, (e) adequate funds, (f) flexible and realistic management, (g) supportive environment, (h) quality teaching and learning process.